Peningkatan Keterampilan Pembuatan Catu Daya Variable Bagi Guru SMK - Hastuti Hastuti; Habibullah Habibullah; Dwiprima Elvanny Myori (JTEV (Jurnal Teknik Elektro dan Vokasional), 2019)
SMK N 1 Koto XI Tarusan is one of the SMK’s that develops new study programs namely Teknik Audio Video (TAV), one of the goals is to prepare the students to have the skills to enter employment in companies engaged in electronics in addition to continuing to the level of higher education. Department of Audio Video Engineering is more directed to the electronics field, but in all teaching and learning activities especially practical activities using equipment related to electricity, such as power supplies. But they do not have good knowledge about power supplies because power supplies are basic knowledge of electricity that is not specifically studied in the field of Audio Video Engineering. Thus, teachers must be equipped with adequate skills, so that these skills can be transferred to their students. The provision of skills for these teachers is carried out by providing training in making power supplies with variable outputs. The method of conducting training is direct practice, with 3 stages. The first stage was that participants were given knowledge about power supply theory, about how to design power supply circuits and calculate component and design requirements. The second or core stage, the trainees did the practice of making layouts, the practice of designing the power supply, the practice of calculating the value of the components needed, and assembling the power supply itself such as making a PCB layout, and making a variable power supply trainer. While, the third stage or the final stage is troubleshooting to test the power supply that is made to function properly/not. The training that was carried out was also analyzed with several indicators to see whether the training provided an increase in skills to the participants/not. From the training that has been carried out, the trainees can make 10 sets of 0-30 Volt variable power supplies that can be functioned properly. The training can also improve the participants' skills which are analyzed from several indicators: learning, behavior, reaction, and results. Testing with these indicators shows that the implementation of the training has provided profound benefits and is very helpful in improving the participants' self quality. Keywords: Training, Skill Improvement, Variable Power Supply